Response to Nitrogen Deficiency and Compensation on Physiological Characteristics, Yield Formation, and Nitrogen Utilization of Rice - Xiong, Qiangqiang; Tang, Guoping; Zhong, Lei; He, Haohua; Chen, Xiaorong (Frontiers in Plant Science, 2018)
Based on ecological crop nutrient deficiency and compensation effect theory, the nitrogen (N) sensitive stage of rice (Oryza sativa L.) was selected to study N deficiency at tillering stage and N compensation at young panicle differentiation stage. Four nitrogen treatments were treated and the effects of N deficiency and compensation were investigated on grain yield, N uptake and utilization and the physiological characteristics of rice. The results showed that the yield per plant presented an equivalent compensatory effect. Double N compensation led to superiority in the number of effective panicles per plant, increased activities of nitrate reductase (NR) and glutamine synthetase (GS), the content of endogenous growth-inhibitory hormone (ABA) decreased in the leaves, photosynthesis was enhanced, and the number of tillers per plant increased. During maturation stage, the panicle dry mass in T1(after N deficient conditions at tillering stage, double N compensation at young panicle differentiation stage) was higher than that in CK1(constant supply of N throughout different stages of growth) and the biomass per plant in T1 increased by 1.47% compared to CK1. N contents in all organs, N accumulation and total N content were all higher in T1 during maturation stage. Moreover, optimized N agronomic efficiency (AEN), N recovery use efficiency (REN), N harvest index (HIN), N physiological efficiency (PEN) and N partial factor productivity (PFPN) were enabled for T1 compared to CK1. This study contributes to the understanding of the physiological mechanisms underlying the compensation of N deficiency in rice.